Philanthropy and education: strategies for impact - Thümler, Ekkehard; Bögelein, Nicole; Beller, Annelie; Anheier, Helmut K. (Palgrave Macmillan, 2014)
Philanthropic foundations play an increasingly important role in attempts to enhance the performance of school systems. Based on case studies from Germany, Switzerland and the US, this book develops an innovative model of effective education philanthropy for successfully tackling problems in the complex field of education.
Literaturangaben
Keywords: Bildungsförderung; Bildungspolitik; Pädagogik; Bildung